Correlation Between Immunohistochemistry and Sequencing in H3G34-Mutant Gliomas. (February 2021) - Gianno, Francesca; Antonelli, Manila; Di Dio, Tiziano; Minasi, Simone; Donofrio, Vittoria; Buccoliero, Anna M.; Gardiman, Marina P.; Pollo, Bianca; Diomedi Camassei, Francesca; Rossi, Sabrina; Novello, Mariangela; Giangaspero, Felice; et al.
Abstract : Recurrent glycine-to-arginine/valine alterations at codon 34 (G34R/V) within H3F3A gene characterize a subset of hemispheric high-grade gliomas (HGG) affecting children and young adults. These tumors, defined as G34R/V-mutant gliomas, are histologically heterogenous, with microscopic features of either HGG or embryonal tumors (primitve neuroectodermal tumor-like features). To assess the value of immunohistochemistry (IHC) to detect G34R/V -mutated cases, we tested anti-histone G34V (clone 329E5) and anti-histone G34R (clone RM240) antibodies in a series of 28 formalin-fixed and paraffin-embedded samples. A total of 28 cases of hemispheric, IDH -wt HGG mainly affecting children and young adults were evaluated by IHC and by sequencing. The median age of patients at diagnosis was 17 years (0.1 to 26 y). By IHC, 10 of the 28 cases showed nuclear positivity for G34R and 3 of the 28 cases for G34V. Molecular analysis of G34R/V-mutation status was successful in 24 of the 28 cases. Mutation at glycine 34 of the H3F3A gene was identified in 9 of the 24 tumors (37%) by direct sequencing, revealing 7 of 9 positive case by sequencing and 2 of 9 false negative cases by IHC. Two of 15 negative case by sequencing demonstrated a false positivity by IHC. In total, in 4 (16.6%) of 24 cases, IHC and mutational results were discordant: 2 tumors were negative by IHC (false negative) but harbored G34R mutation by sequencing, and 2 cases were positive by IHC (false positive by IHC) but wild type by sequencing. Moreover, most mutated cases showed loss of ATRX expression and/or p53 expression. The positivity by IHC with specific antibody tested is not highly predictive for presence of G34R/V mutation, but confirmation by sequencing is mandatory; G34R/V mutations should be suspected in all hemispheric tumor IDH1/2 wild type, showing loss of OLIG2 and ATRX and/or p53 expression.